2008
DOI: 10.1182/blood-2008-01-132092
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine storm in a mouse model of IgG-mediated hemolytic transfusion reactions

Abstract: Cytokines are hypothesized to play a central role in the pathophysiology of IgGmediated hemolytic transfusion reactions (HTRs), and deeper understanding is required for improving therapy for these events. After establishing well-defined mouse models of HTRs, we tested whether cytokines were involved. Red blood cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 25 publications
3
39
0
2
Order By: Relevance
“…Similarly, the ability of anti-GPA to induce Ag modulation demonstrates that Ag modulation is not limited to anti-Fy3. The unique biphasic clearance pattern induced by anti-GPA is consistent with previous studies (35). Given the potential involvement of complement in anti-GPA-mediated clearance (40), complement receptors may initially trap RBCs following Abmediated complement deposition and then release some RBCs following subsequent complement degradation, as suggested by previous studies examining the consequences of complement deposition on RBCs (36,41).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, the ability of anti-GPA to induce Ag modulation demonstrates that Ag modulation is not limited to anti-Fy3. The unique biphasic clearance pattern induced by anti-GPA is consistent with previous studies (35). Given the potential involvement of complement in anti-GPA-mediated clearance (40), complement receptors may initially trap RBCs following Abmediated complement deposition and then release some RBCs following subsequent complement degradation, as suggested by previous studies examining the consequences of complement deposition on RBCs (36,41).…”
Section: Discussionsupporting
confidence: 85%
“…Although nonimmunized recipients failed to clear double Ag + cells, anti-Fy3-immunized and anti-GPA-immunized recipients each effectively cleared double positive cells (Fig. 9A), consistent with previous results and those of this study (35). Examination of bound Ab and detectable Ag demonstrated that Ab could be detected only on double Ag + cells following transfer into immunized recipients and that double positive RBCs experienced modulation of HOD Ag, but not GPA Ag, following transfer into anti-Fy3-immunized recipients (Fig.…”
Section: Decrease In Detectable Ag Extends Intra-but Not Intermoleculsupporting
confidence: 92%
“…In malaria, as in diseases with release of Hb from RBCs, there is uncontrolled inflammatory imbalance and intense oxidative stress (2,(38)(39)(40). In this paper, we report that patients with severe P. vivax infection, similar to individuals and mice with falciparum malaria (22, 33, 41), displayed reduced plasma levels of PGE 2 and TGF-b than those with mild infections, with this reduction being inversely proportional to the bilirubin, total heme, and SOD-1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms mediating the severe complications of HTRs in SCD patients are unknown, and no specific therapy is available. Because inflammatory cytokines and chemokines are important in the pathogenesis of acute and delayed HTRs and in SCD crises (10,(12)(13)(14), they may be involved in the serious and specific clinical manifestations of HTRs found in SCD patients.…”
Section: Introductionmentioning
confidence: 99%
“…IgG-mediated HTRs involve complement activation, phagocytosis, cytokine production, and various cellular responses (8)(9)(10)(11). In SCD, HTRs can precipitate acute VOC or hyperhemolysis syndrome, resulting in significant morbidity (5-7).…”
Section: Introductionmentioning
confidence: 99%